The revaluation of written language from the point of view of Jacques Derrida (Devenires, 2005)
When studying Language, Linguistics has its field in the study of the methods of investigation and the theoretical issues common to all the variety of languages. However, when analyzing the phenomenon of writing it confines it to the grammatical field and pinpoints how the laws of combination and relational structure of written signs should be, but it does not inquires into the own genesis of writing or its productive process. On the other hand, nowadays we have coexisting at least two disciplines of philosophical nature intimately related to Language: Semiology and Semiotics. Again both touch tangentially the problem of writing; in fact this has occupied a marginal place in Philosophy of Language and Hermeneutics. Jacques Derrida was always very surprised to see that almost all the Occidental culture favors the spoken language. In contrast, written language barely could be an image or representation, a copy or an auxiliary tool of the spoken language. There for the importance of the revolutionary and innovative undertaking of this philosopher, that is, to rescue and value the written language by itself to make of it an essential part of philosophical reflections and the target of study of an specific discipline...
Keywords: Jacques Derrida; writing; language